Sperm abnormalities in the dog : a light and electron microscopic study - Oettlé, Edmund Eric (Division of Cell Biology, 2018)
This thesis is a systematic description of normal and abnormal dog spermatozoa by means of bright field light and transmission electron microscopy, and an investigation into the effect that abnormal sperm have on canine fertility. A total of 101 ejaculates were collected from 88 dogs, of 34 different breeds. Sperm samples were examined macroscopically for volume, colour, consistency, and pH. Microscopic evaluation of sperm motility was conducted on all samples. Morphological evaluation using light microscopy was conducted on 71 of the samples. Samples from 10 of the dogs were examined ultrastructurally. A novel classification for abnormal dog sperm is presented. Abnormal sperm were classified into one of the following groups: Acrosomal defects, head defects, midpiece defects, tail defects and other abnormalities. Abnormalities were further sub-divided into major and minor defects. The most common abnormalities encountered were major sperm head defects. The abnormalities are compared with those described for other species, in particular the bull and man. The association between the percentage abnormal sperm in the ejaculate and the fertility of the dog was statistically evaluated. On this basis, the dogs were divided into normal and sub-normal groups. The percentage normal morphology below which fertility was adversely affected was found to be sixty percent. The fertility of dogs with greater than or equal to 60 percent normal morphology was 61 percent, while the fertility of dogs with · less than 60 percent normal morphology was 13 percent. There was no statistical difference between the ages of the dogs in the two groups; from this it was concluded that sub-fertility may affect a dog at any age. A means of evaluating dogs for reproductive potential is discussed.